Identifying Causes of Vaginal Discharge: The Role of Gynecologic Symptoms and Signs - Farhan D Hasan; Dwiana Ocviyanti (Indonesian Socety of Obstetrics and Gynecology, 2015)
Abstract Objective: To attain diagnostic accuracy of various gynecologic symptoms and signs in identifying causes of vaginal discharge. Method: Eighty-two subjects were included in this cross sectional study. Gynecologic symptoms and signs were inquired from each subject and further laboratory examinations were carried out to identify the etiology. Diagnostic accuracy for each symptom and sign was compared to the laboratory examination as the standard reference. Symptoms and signs with positive predictive value (PPV) of more than 50% were considered to have good diagnostic accuracy. Result: For bacterial vaginosis, excessive wetness in genital area; vulvar maceration; and thin, turbid, yellowish vaginal discharge had PPVs of 53%; 52%; and 52%, respectively. For candidal vaginitis, vulvar maceration; and white, curd-like vaginal discharge had PPVs of 58% and 100%, respectively. For trichomoniasis, thin, turbid, frothy, yellowish vaginal discharge; and strawberry-cervix appearance had PPVs of 60% and 100%, respectively. There were no symptoms or signs with PPV of more than 50% for chlamydial cervicitis. Diagnostic accuracy for clinical findings in gonorrheal cervicitis could not be calculated due to the small number of subjects. Conclusion: Various gynecologic symptoms and signs were found to be accurate in diagnosing bacterial vaginosis, candidal vaginitis, and trichomoniasis. No symptoms or signs were considered accurate to aid etiological diagnosis for chlamydial and gonorrheal cervicitis. Keywords: bacterial vaginosis, Candida sp, Chlamydia trachomatis, gynecologic symptoms and signs, Neisseria gonorrhoeae, Trichomonas vaginalis